EFEKTIVITAS METODE BERMAIN TERHADAP KEMAMPUAN BERHITUNG PERKALIAN SISWA SEKOLAH DASAR - Chaidir, Liya; Ramadhani, Dita Mulyana; M, Irmawati; Hasanah, Uhwah; St Harpiani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
Abstract:The aim of this research is to improve student learning outcomes in mathematics learning for grade III elementary school. Specifically, this research aims to increase students' knowledge of multiplication operations using the play method in class III elementary school students. The research method used in this research is classroom action research (PTK). This research used two cycles. In each observation cycle, observations are carried out using data collection techniques in the form of planning, action, observation and reflection. The results of research in cycle 1 obtained an average learning outcome value of 61.46 with a total of 13 students. Then 7 students completed and 6 students did not complete. The highest score obtained by students was 93 and the lowest score was 24. The classical completeness percentage was set at 70% and student learning outcomes in cycle I did not meet the completeness criteria because the student completeness percentage value was only 53.84%. In cycle II, the average value of student learning outcomes was 81.38 with the number of students being 13 people. Then 12 students completed and 1 student did not complete. The highest score obtained by students was 97 and the lowest score was 55. The class completion percentage was 92.30% so that student learning outcomes in cycle II met the minimum completion criteria of 70%. From the data above, the average score obtained for students in cycle I was 61.46, while in cycle II the average score was 81.38. So it can be concluded that there is an increase in student learning outcomes in cycle I and cycle II.